(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
This paper draws attention to links between aesthetic engagement and pre- and in-service teacher self- identity. Generally, my students have little or no background in art or art education. The courses, both graduate and undergraduate, are electives. The paper is divided into two parts. Part 1 begins with an overview of terms and concepts associated with aesthetics and argues for attention to ‘engagement’ rather than ‘experience’. Further, it argues for inclusion of classes in aesthetic engagement throughout public school education as preparation for, and participation in, what Maxine Greene has called ‘wide-awakeness’. That state of being involves an understanding of the place of imagination, empathy, and value discernment in education, and teachers’ moral duty. Part 2 introduces two strategies for prompting engagement with artworks through evocative writing, a ‘show’ versus ‘tell’ emphasis. The writing has a pedagogical goal: to assist in the sharing of experiences so that the teacher can guide students to enlarged aesthetic encounters. But teachers must also engage in writing their own evocative responses, to gain some grasp of the possible range of aesthetic responses and thus achieve credibility in their teaching of aesthetic engagement. Thus, the examples are meant as guides to students and teachers alike. The paper concludes with an example of ‘found’ poetry regarding a particular artwork, followed by the author’s poem devoted to the same artwork.